KEPUASAN KONSUMEN, HARGA, PROMOSI DAN KUALITAS PELAYANAN TERHADAP LOYALITAS MEREK MOTOR YAMAHA - Imu Aristiyanto, 08.05.51.0165; Kasmari, Kasmari (Students Journal of Economic and Management, 2012)
Through the questionnaire method by using purposive sampling technique on 100 respondents who use Yamaha motor products. While the population is used as respondents in this study is the first Kesatrian Semarang High School Students. Where the variable Brand Loyalty, Customer Satisfaction, Price, Promotion, and Quality of Service. Testing the hypothesis using the t test showed that the four independent veriabel studied is found to significantly affect the dependent variable Brand Loyalty. Then through the F test can be seen that all the independent variables is feasible to test the variables depanden Loayalitas Brand. Figures Adjusted R Square of 0.230 indicates that 23% of the variation can be explained by Brand Loaylitas four independent variables in the regression equation. While the rest of 77% is explained by variables other than the interface of the four variables in this study.Key words : brand loyalty, customer satisfaction, pricing, promotion, quality of service